Making market women : gender, religion, and work in Ecuador - DeTemple, Jill Michelle (University of Notre Dame Press, 2020)
"Making Market Women tells of the initial success, and later failure, of a liberationist Catholic women's cooperative in central Ecuador. Jill DeTemple argues that when gender and religious identities are capitalized, they are made vulnerable. Using archival and ethnographic methods, she shares the story of the women involved in the cooperative, producing cheese and knitted goods for local markets, and places their stories in the larger context of both the cooperative and the community. DeTemple explores the impact of gender roles, the perception of women, the growing middle class, and the changing mode of Catholicism in their community. Although the success may have been due to group cohesion to the identity of Catholic women, the failure of the cooperative left many women less sure of these identities. They keep their Catholic identity but blame the institutional church in some ways for the failure and are less confident in their ability as women to compete successfully in market economies. Because DeTemple examines not only the effects of gender and religion on development but also the effects of development, successful or unsuccessful, on the identities of those involved, this book will interest scholars of international development, religious studies, Latin American studies, anthropology, and women's studies"--